A atuação do judiciário Tocantinense em face dos processos sobre violência sexual contra menores: uma perspectiva da garantia e efetivação de direitos - Magalhães, Alyne Crystina Alves (Universidade Federal do Tocantins, 2021)
In this article we will study the sexual violence of minors in the state of Tocantins, its causes, consequences and action of the local judiciary regarding this issue, considering it is a recent court. To this end, national and international legislation related to the protection of children and adolescents will be analyzed, observing its effectiveness and application. We will also discuss the evolution of the concept of children in the Brazilian legal system and the way until this public became subject of rights. In addition, we will reflect on the importance of human rights in combating juvenile sexual violence, and applying the principle of the best interests of the child, especially in the recurring cases of intrafamilial sexual violence.